2021
DOI: 10.1186/s40795-021-00445-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for overweight and obesity among women of reproductive age in Dar es Salaam, Tanzania

Abstract: Background Overweight and obesity have increased considerably in low- and middle-income countries over the past few decades, particularly among women of reproductive age. This study assessed the role of physical activity, nutrient intake and risk factors for overweight and obesity among women in Dar es Salaam, Tanzania. Methods We conducted a cross-sectional survey among 1004 women aged 15–49 years in the Dar es Salaam Urban Cohort Study (DUCS) fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
5
13
0
1
Order By: Relevance
“…This study indicated that discretionary calories per week are associated with overweight among 20–49 years age of women. This finding is similar to other findings from Dar es Salaam, Tanzania [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study indicated that discretionary calories per week are associated with overweight among 20–49 years age of women. This finding is similar to other findings from Dar es Salaam, Tanzania [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Women having higher monthly incomes were 3.916 times more likely to have overweight as compared to women who have lower monthly incomes. This finding is similar to other studies in different parts of Ethiopia ([ 28 ]) [ 34 ]; Dar es Salaam, Tanzania ([ 35 ]); Zimbabwe [ 31 ]; and Kenya [ 32 ]. This might be due to their capacity to purchase more energy-dense foods, as witnessed by studies in both developed and developing countries that show high-income households purchasing foods from supermarkets.…”
Section: Discussionsupporting
confidence: 91%
“…The lowest percentage of the score on the overall balance component, including ratio PUFA to SFA and MUFA to SFA, was 8% and ratio macronutrient. The diet quality measurement based on the DASH score reported no significant association between dietary quality and obesity indicators [40]. Similar results had been reported that after adjusting for age, sex, energy intake, physical activity, and smoking status, multivariate analysis of covariance did not show any significant results regarding diet quality indices' in Tehran [42].…”
Section: Discussionsupporting
confidence: 75%
“…In the study, overweight and obesity, central obesity, are more prevalent among women than male participants. In Tanzania, the risk of overweight/obesity was higher among older women (PR 1.59; 95% CI: 1.30-1.95), [40]. A high prevalence of maternal obesity is reported in a systematic review and meta-analysis across Africa, 6.5−50.7% [41].…”
Section: Discussionmentioning
confidence: 98%
“…26 Similarly other African studies have identified that the risk for overweight/obesity was higher among older women. [27][28][29][30] The mechanisms responsible for this age-associated risk with gestational weight gain may be linked to metabolic dysfunction and alterations in the deposition of adipose tissue. 31 Gestational age in this study was also positively associated with overweight and obesity in both HIV-infected and HIV-uninfected pregnant black South African women.…”
Section: Discussionmentioning
confidence: 99%